A high precision shooting and bouncing rays method without mesh for scattering calculation of complex target. (24th April 2019) - Li, Jianzhou; Li, Shuang
Abstract: To extend the application of shooting and bouncing rays (SBR) method in the penetration structure and further improve the calculation accuracy, an improved mesh free SBR method that completely implements ray‐tracing and electromagnetic computing in 3‐D geometrical modeling software is proposed. The basic idea is to combine the non‐uniform rational b‐splines (NURBS) surface modeling function and open application programming interface (Open API) to implement the process of mesh free ray tracing, which greatly improve calculation accuracy and efficiency of SBR. Based on this, the improved SBR method can yield a superior performance for scattering analysis of complex targets, especially at the problem where reflected and transmitted waves exist simultaneously in a target. The numerical results demonstrate that the improved SBR is highly effective in computing scattering fields of complex targets.